On the structure and properties of silver nanoparticles - Gracia Pinilla, Miguel Ángel; Pérez Tijerina, Eduardo; Antúnez García, Joel; Fernández Navarro, Carlos Javier; Tlahuice Flores, Alfredo; Mejía Rosales, Sergio; Montejano Carrizales, Juan Martín; Yacamán, Miguel José (American Chemical Society, 2008)
Silver tetrahedral nanoparticles (NP) were synthesized using the inert gas condensation technique. We performed morphological and optical characterization of the nanoparticles (NPs) using atomic force microscopy (AFM), mass spectroscopy (MS), and UV-visible spectroscopy. The Ag NPs were produced by modified magnetron sputtering, followed by thermalization and condensation in a high pressure zone. Along the synthesis process, the size of the NPs was controlled through the handling of the gas flow (Ar and He), the magnetron power, and the length of the aggregation zone. We optimized the synthesis parameters to obtain a peak on the size distribution of Ag NPs around of 5 nm (as measured with AFM and MS). The AFM measurements show that the particles have tetrahedral shape, with a fair correspondence with a 2925-atoms ideal tetrahedron. We performed a set of Molecular Dynamics (MD) calculations using the Embedded Atom potential model to simulate the dynamics of particles with different shapes, obtaining that, at sizes close to that of the particles produced experimentally, the tetrahedra may be as energetically stable as cuboctahedra of roughly the same size, and that their melting point is below but close to that of the bulk. We also found that both the size and shape of the nanoparticles determine the shift of the UV-visible absorption spectrum. Finally, we observed the formation of atomic islands above the faces of the Ag tetrahedral NPs, in agreement with the results obtained from the MD simulations.